Malnutrition is associated with six-month mortality in older patients admitted to the emergency department with hip fracture - Franz, Kristina; Deutschbein, Johannes; Riedlinger, Dorothee; Pigorsch, Mareen; Schenk, Liane; Lindner, Tobias; Möckel, Martin; Norman, Kristina; Müller-Werdan, Ursula (Frontiers in Medicine, 2023)
Background Hip fractures in older people are a common health problem often associated with malnutrition that might affect outcomes. Screening for malnutrition is not a routine examination in emergency departments (ED). This analysis of the EMAAge study, a prospective, multicenter cohort study, aimed to evaluate the nutritional status of older patients (≥ 50 years) with hip fracture, factors associated with malnutrition risk, and the association between malnutrition and the six-months mortality. Methods Risk of malnutrition was evaluated using the Short Nutritional Assessment Questionnaire. Clinical data as well as data on depression and physical activity were determined. Mortality was captured for the first six months after the event. To assess factors associated with malnutrition risk we used a binary logistic regression. A Cox proportional hazards model was used to assess the association of malnutrition risk with six-month survival adjusted for other relevant risk factors. Results The sample consisted of N = 318 hip fracture patients aged 50 to 98 (68% women). The prevalence of malnutrition risk was 25.3% (n = 76) at the time of injury. There were no differences in triage categories or routine parameters measured in the ED that could point to malnutrition. 89% of the patients (n = 267) survived for six months. The mean survival time was longer in those without malnutrition risk (171.9 (167.1–176.9) days vs. 153.1 (140.0–166.2) days). The Kaplan Meier curves and the unadjusted Cox regression (Hazard Ratio (HR) 3.08 (1.61–5.91)) showed differences between patients with and patients without malnutrition risk. In the adjusted Cox regression model, risk of death was associated with malnutrition risk (HR 2.61, 1.34–5.06), older age (70–76 years: HR 2.5 (0.52–11.99); 77–82 years: HR 4.25 (1.15–15.62); 83–99 years: HR 3.82 (1.05–13.88)) and a high burden of comorbidities (Charlson Comorbidity Index ≥3: HR 5.4 (1.53–19.12)). Conclusion Risk of malnutrition was associated with higher mortality after hip fracture. ED parameters did not differentiate between patients with nutritional deficiencies and those without. Therefore, it is particularly important to pay attention to malnutrition in EDs to detect patients at risk of adverse outcomes and to initiate early interventions.